Factors Affecting the Sustainable Development of the Logistics Industry: A Study in Thanh Hoa Province, Vietnam - Dao Hong Van (Mathematical Statistician and Engineering Applications, 2022)
Logistics is a crucial component in putting Thanh Hoa province’s sustainable development plan into practice both now and in the future, especially in the context of globalization and the fourth industrial revolution. According to research, logistics has a favorable effect on three different aspects of sustainable development: (I )sustained economic growth; (ii) ensuring social fairness; and (iii) maintaining a healthy environment.